Anthropometrics Related to the Performance of a Sample of Male Swimmers. Issue 3 (June 2014) - Perciavalle, Valentina; di Corrado, Donatella; Scuto, Claudia; Perciavalle, Vincenzo; Coco, Marinella
The main purpose of the present investigation of 21 elite male swimmers was to assess whether the Ape Index (the ratio between the individual's arm span and height) and/or the second-to-fourth digit length ratio (2D:4D), i.e., the ratio between the length of the second and the fourth fingers of the right hand, are associated with the performance of high-level swimmers, when mood and / or executive function are covaried. The results showed no statistically significant correlation between the Ape Index and 2D:4D ratio, performance, executive function, or mood. In contrast, statistically significant correlations were found between 2D:4D ratio and performance, executive function, and mood. Regressions indicated that 2D:4D ratio and not Ape Index is related to the performances of a sample of male swimmers.